(3GdJPcQIs - (3GdbQWHjs
(3ChdgG (B:s
(3hUa GdMSf Hf Sgd GdMf abGd(B: (3ajgG JeMjU GdPfH ai JJHYg ef GdZadI ,hJYQjV ddKhGH HGdUHQ s
(3BNQgG (B:s
(3MceI ddTGaYi(B:(3Jhb ef GdGjGe SHYG chGedG s
(3cJGH ai GdCOH LGA ai gGeT hQbI (B86(3C YfO Chd GdHGH GdYTQjf YHGQI (B: (3GdbQWHi ai GdJPcQI ef cdGe Ydi Hf CHj WGdHs
(3hgj ChQGb eJaQbIs
(3hJTJed Ydi BNQ GdHGH (B19 (3, hGdHGH (B20 (3,(B21(3, hJHOC HGdhQbI (B47(3C(B-94(3CjJNddgG ChQGb ef cJH CNQi hHNW eZGjQ ef hQbI (B55(3H(B_86(3C YHGQg Yfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B160 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs